2023
DOI: 10.3171/2022.9.jns221565
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound–mediated blood-brain barrier opening in Alzheimer’s disease: long-term safety, imaging, and cognitive outcomes

Abstract: OBJECTIVE MRI-guided low-intensity focused ultrasound (FUS) has been shown to reversibly open the blood-brain barrier (BBB), with the potential to deliver therapeutic agents noninvasively to target brain regions in patients with Alzheimer’s disease (AD) and other neurodegenerative conditions. Previously, the authors reported the short-term safety and feasibility of FUS BBB opening of the hippocampus and entorhinal cortex (EC) in patients with AD. Given the need to treat larger brain regions beyond the hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 48 publications
1
37
1
Order By: Relevance
“…With BBB limiting an estimated 99.8 % of peripherally administered large molecule drugs such as therapeutics antibodies (95), we next tested the possibility of enhancing the permeabilisation of ALS BBB to large molecules with FUS +MB . As a proof-of-concept, we trialled the delivery of anti-TDP-43 antibody, considering promising preclinical development of TDP-43 targeted immunotherapies (96)(97)(98)(99) as well as the recent clinical success of therapeutic antibodies in the treatment of other neurodegenerative disorders (100)(101)(102)(103)(104). Although the utilised anti-TDP-43 antibody has not yet proved therapeutically beneficial, we were previously successful in delivering Aducanumab (Aduhelm TM ) and anti-tau therapeutic antibodies with FUS +MB in human Alzheimer's disease in vitro models (37,41); and a recent clinical study demonstrated beneficial effects of Aducanumab combined with FUS +MB in Alzheimer's disease patients, as compared to Aducanumab alone (104).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With BBB limiting an estimated 99.8 % of peripherally administered large molecule drugs such as therapeutics antibodies (95), we next tested the possibility of enhancing the permeabilisation of ALS BBB to large molecules with FUS +MB . As a proof-of-concept, we trialled the delivery of anti-TDP-43 antibody, considering promising preclinical development of TDP-43 targeted immunotherapies (96)(97)(98)(99) as well as the recent clinical success of therapeutic antibodies in the treatment of other neurodegenerative disorders (100)(101)(102)(103)(104). Although the utilised anti-TDP-43 antibody has not yet proved therapeutically beneficial, we were previously successful in delivering Aducanumab (Aduhelm TM ) and anti-tau therapeutic antibodies with FUS +MB in human Alzheimer's disease in vitro models (37,41); and a recent clinical study demonstrated beneficial effects of Aducanumab combined with FUS +MB in Alzheimer's disease patients, as compared to Aducanumab alone (104).…”
Section: Discussionmentioning
confidence: 99%
“…As a proof-of-concept, we trialled the delivery of anti-TDP-43 antibody, considering promising preclinical development of TDP-43 targeted immunotherapies (96)(97)(98)(99) as well as the recent clinical success of therapeutic antibodies in the treatment of other neurodegenerative disorders (100)(101)(102)(103)(104). Although the utilised anti-TDP-43 antibody has not yet proved therapeutically beneficial, we were previously successful in delivering Aducanumab (Aduhelm TM ) and anti-tau therapeutic antibodies with FUS +MB in human Alzheimer's disease in vitro models (37,41); and a recent clinical study demonstrated beneficial effects of Aducanumab combined with FUS +MB in Alzheimer's disease patients, as compared to Aducanumab alone (104). Hence, we hypothesised that analogously, achieving increased permeability of this model anti-TDP-43 antibody in our cell platform could be representative of future clinically approved ALS immunotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that, in some instances, the BBB integrity could already be compromised by the occurring disease [48], thus facilitating the trafficking of antibodies to the brain, the improvement of antibody delivery in the CNS is an area of active research. Recently, Alzheimer's disease researchers used focused ultrasound to disrupt specific sections of the BBB, leading to an improved penetration of antibeta-amyloid antibodies into the brain, focally enhancing the removal of amyloid plaques [49 ▪ ]. Increased transport through the BBB could also be achieved by creating antibodies with improved binding to Fc Receptor [50 ▪ ] or with bifunctional properties [51].…”
Section: Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…The primary objective of the study is to assess the safety and feasibility of FUS-induced BBBO in Alzheimer's disease patients, using a portable, noninvasive FUS system. Secondary objectives includes testing the feasibility of cavitation mapping and observing changes in 18 F-Florbetapir PET and in blood biomarkers. Six Alzheimer's disease patients (2M/4F, age = 69.7±7.2 yr) were enrolled in a phase 1 trial under FDA and Columbia University IRB approval (NCT04118764) (Table 1).…”
Section: Study Overviewmentioning
confidence: 99%
“…Figure 7 shows the percent changes in standard uptake value ratio (SUVR) or asymmetry SUVR of 18 F-Florbetapir compared to the baseline. Subject 3 was excluded due to the absence of BBBO.…”
Section: A Modest Decrease In Asymmetry Suvr Correlated With the Size...mentioning
confidence: 99%